The impact of a footwork training program on developing coordination skills and improving forehand and backhand strokes for players of the Durrat Karbala Tennis Club - Hassan, Alaa Rahim; Diaa, Barakat Muhammad Ali; Al-Saadi, Ali Subhi Hussein (Sulaimani Journal for Humanities, 2026)
The research problem lies in the significant role of leg and foot movements in a player's performance level. Coordination and agility in these movements are crucial in determining the outcome of many matches. The research aims to develop a footwork training program and to identify the impact of this program on certain coordination abilities and the forehand and backhand stroke skills of players from the Durrat Karbala Tennis Club. The researchers employed a two-group experimental design and purposively selected ten young players (under 16 years old) from the Durrat Karbala Tennis Club in Karbala Governorate. After ensuring homogeneity and equivalence of the study variables, the necessary tests were determined after consulting experts and reviewing scientific literature. These tests consisted of two assessments of coordination abilities and two skill tests for the forehand and backhand strokes. A pilot test of the developed tests was then conducted, followed by pre-tests and the initiation of specific leg muscle exercises and training. Footwork was used for a month and a half, with the use of different training tools and methods, which contributed to the development of the study variables. This was demonstrated through the statistical treatments of the research variables. The most important conclusions were that the exercises using footwork proved their efficiency and method of operation by helping the players to train. The exercises are a valid method that fulfills the purpose through which they contributed to stimulating the players and completing the exercises with a high degree of accuracy and focus. The researchers recommended that coaches adopt and benefit from the special exercises that were designed in the training process of tennis players and other similar sports in developing their skill and physical efficiency.